Outcome of high‐power short‐duration radiofrequency ablation in combination with half‐normal saline irrigation for the treatment of atrial fibrillation. Issue 1 (10th December 2021) - Maan, Abhishek; Bode, Weeranun D.; Heist, E. Kevin; Ha, Grace; Carnicelli, Anthony; Slattery, Kathryn; Fitzsimons, Michael; Ruskin, Jeremy; Mansour, Moussa
Abstract: Background: Data regarding the use of high‐power short‐duration (HPSD) radiofrequency (RF) in combination with half‐normal saline irrigation for catheter irrigation are limited. Objectives: This study investigated the safety and efficacy of using HPSD RF ablation in combination with half‐normal saline irrigation for the treatment of AF. Methods: One hundred consecutive patients with AF underwent RF ablation using HPSD combined with half‐normal saline for catheter irrigation. In addition, the following ablation strategies were used: 1 mm tags for the display of ablation lesions on the mapping system, high‐frequency jet ventilation (HFJV), low contact force, pacing after ablation to verify areas of noncapture, atrial/ventricular pacing at 500 to 700 ms to aid in catheter stability, use of two skin electrodes to reduce impedance, and postablation adenosine infusion. Power was started at 40 to 45 W and was modulated manually based on impedance changes. Results: The average age of patients was 65.2 years and 70% were male. Forty seven percent had paroxysmal AF and the average CHA2 DS2 ‐VASc score was 2.1 ± 1.6. The average power and lesion duration were 38.1 ± 3.3 W and 8.1 ± 2.3 s, respectively. During a median follow‐up period of 321 ± 139 days, 89% of the patients remained free from any atrial arrhythmias after a single RF ablation procedure. No procedure‐related death, stroke, pericardial effusion, or atrioesophageal fistula occurred during follow‐up. Conclusions: Catheter ablation using HPSD RF lesions in combination with half‐normal saline irrigation and is safe and effective, and results in high rate of freedom from AF.